2020
DOI: 10.3390/agronomy10010138
|View full text |Cite
|
Sign up to set email alerts
|

Using Digestate and Biochar as Fertilizers to Improve Processing Tomato Production Sustainability

Abstract: The principal goal of the organic farming system (OFS) is to develop enterprises that are sustainable and harmonious with the environment. Unfortunately, the OFS yields fewer products per land than the non-organic farming system in many agricultural products. The objective of our study was to assess the effects of digestate and biochar fertilizers on yield and fruit quality of processing tomato produced under the OFS. The experiment was carried out in Po Valley, during the 2017 and 2018 growing seasons. Liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 63 publications
12
33
0
Order By: Relevance
“…According to Article 4 of the Act, the central governing agency shall announce the categories, types, and specifications of fertilizers, including nitrogen fertilizer, phosphorus fertilizer, potassium fertilizer, minor trace elements fertilizer, organic matter fertilizer, compound fertilizer, plant growth aid, microbial fertilizer, and other fertilizers. Obviously, the biogas digestate belongs to one of the organic matter fertilizers due to its richness in soil nutrients [14][15][16][17][18][19][20]. Table 3 lists the composition specifications/limits of organic matter fertilizers (livestock manure compost item No.…”
Section: Fertilizer Management Actmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Article 4 of the Act, the central governing agency shall announce the categories, types, and specifications of fertilizers, including nitrogen fertilizer, phosphorus fertilizer, potassium fertilizer, minor trace elements fertilizer, organic matter fertilizer, compound fertilizer, plant growth aid, microbial fertilizer, and other fertilizers. Obviously, the biogas digestate belongs to one of the organic matter fertilizers due to its richness in soil nutrients [14][15][16][17][18][19][20]. Table 3 lists the composition specifications/limits of organic matter fertilizers (livestock manure compost item No.…”
Section: Fertilizer Management Actmentioning
confidence: 99%
“…As mentioned above, digestate is a by-product from the AD of the biogas plant production, which is rich in in minerals (such as nitrogen, phosphorus, calcium, and magnesium) and organic matter [14]. In this regard, biogas-digestate has been used as a sustainable fertilizer for crop production in the organic farming system (OFS) [17][18][19][20]. More significantly, the organic agriculture promotion in Taiwan echoed the UN Agenda 2030 for the SDGs.…”
Section: Organic Agriculture Promotion Actmentioning
confidence: 99%
“…Finally, among the organic fertilizers tested in the pot experiment, dewatered slurry displayed the highest value of N mineralized and lost, followed by dewatered and composted slurry and the latter pelleted. Considering these results, the fertilizers showing a high N mineralized with a high capacity to increase soil water retention might be used in the production of crops that require greater availability of N and water such as tomato [34][35][36][37]. Moreover, farmyard manure and composted farmyard manure displayed lower values of N mineralized and lost, probably due to the lower values of the volumetric water content of the growing medium; however, further investigation is required to corroborate this hypothesis.…”
Section: Resultsmentioning
confidence: 98%
“…Innovative biofertilizers such as digestate and biochar were proposed as key components in maintaining long-term soil fertility and in order to increase the marketable yield of processing tomato cultivated in the OFS [8]. From this point of view, the combined effort of agronomists and breeders is required to improve the sustainability of the processing tomato cultivated in the OFS.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the tomato production sustainability, viable alternatives to synthetic plant protection products and fertilizers, such as essential oil, digestate, biochar, and compost tea, were investigated [6,7]. In a recent work, Ronga et al [8] found that the combined use of biochar and digestate increased the marketable yield of processing tomato under OFS. The use of cover crops, such as hairy vetch (Vicia villosa Roth.…”
Section: Introductionmentioning
confidence: 99%